Disease management practices on rubber in Malaysia: strategies and perspectives / Nur Fakriyah Alias - Alias, Nur Fakriyah (Faculty of Plantation and Agrotechnology, 2016)
This study was conducted to identify the incidence of rubber diseases and their control measures practiced in Malaysia. Root disease is the common diseases found on rubber plantations in Peninsular Malaysia and caused by fungi such as Rigidoporous microporous, Phellinus noxious and Ganoderma pseudoferrum. Other pathogens on rubber have been reported in Malaysia such as Oidium heveae, Colletotrichum gloeosporoides, Phytophthora spp, Oidium havea, Neofusicoccum ribis, Corynespora cassiicola, Corticium salmonicolor, etc. Currently, no updated information or scientific reviews with a focus on the major diseases of rubber and their control methods applied in Malaysia. The last update is determine microorganisms that affecting the leaves, tapping panels, stem and roots of rubber with some management options. Thus, this study updates information with regard to the various diseases of rubber and their several effective control strategies in Malaysia.